Transformasi Keris Jawa Dari Karya Seni Rupa Fisis-Simbolis Menjadi Karya Desain Produk - Krishna Hutama (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2015)
Keris is a traditional weapon developed in Java, Madura, Bali, and others. Geographical and environmental influence has resulted in the difference between its function and form as a practical weapon.  In Javanese life, it has been liberated from its limited function as a practical weapon. Keris is no longer a solely a stabbing weapon, but has grown in the Java community to be a sign or social attributes, and became a kind of embodiment of an ideology of philosophy of life. Keris is not just a physical work of art but also s symbolic one. For a reason, there are people who believe that the dagger has a magical power but there are also those who do not believe it. At present, people believing in the magical power of the keris believe that its making is not the business of everyone. For people who do not believe it, its may be done by anyone so there is a mass and commercial keris production in the form of things of product design.Keywords: keris, phyisical work, symbolic meaning, product design